Separation and biosynthesis of value-added compounds from food-processing wastewater: towards sustainable wastewater resource recovery - Lee, Sze Ying (2022)
Effluents from the food-processing sector often contain significant concentrations of valuable resources, e.g., proteins, lipids, antibiotics, and are free of heavy metals and other toxic contaminants. In addition, food processing wastewaters are one of the largest sources of high-strength wastewaters in the World. Hence, food-processing wastewater holds great potential for resource recovery and reuse, creating additional economic value and concomitantly mitigating environmental contamination. Despite all these factors, very little has been done to analyze the composition of these wastewaters and look for valuable products which can then be separated, or to further ferment these complex wastewaters into valuable products. This review summarizes the application of different approaches to upcycle compounds lost within food-processing wastewater streams by regenerating them into value-added products. The physicochemical separation techniques to recover valuable compounds from wastewater, including membrane technology, foam fractionation, precipitation, adsorption, solvent extraction, and aqueous two-phase system, are critically discussed. In addition, the biotransformation approaches based on enzymes or microorganisms utilizing nutrients from food-processing wastewater as low-cost substrates to produce useful products are also addressed. This includes the production of microalgal biomass with high-value intracellular products in wastewater treatment systems. Finally, some possible future research directions to enhance the circular economy in the food processing industry are proposed.